"Transformation of pancreatic secretion with intraduodenal administration of trypsin and amylase with nonspecific substrates for them." (Texas Journal of Medical Science, 2023)
The results of the study on the effects of enter sorbents allowed us to draw a fundamental conclusion, in our view, that the inhibitory influence on the secretion of pancreatic enzymes is exerted by only the solubilized enzymes in the duodenum contents. Immobilized enzymes bound to enter sorbents lose or significantly reduce this ability to inhibit pancreatic secretion. The de-blocking effects are also induced by nutrients introduced intraduodenally. In our laboratory, it has been demonstrated (Korotko G.F., Baybekova G.D.) that starch as a substrate for amylase removes its selective inhibitory effect on the secretion of pancreatic amylase; the selective inhibition of pancreatic protein secretion is reduced by intraduodenal administration of protein, and emulsified fat eliminates inhibitory effects on pancreatic secretion of lipase. The fundamental similarity of effects between sorbents and nutrients, considering the latter as factors immobilizing enzymes, allows us to observe some external analogy between the comparable effects.